The quantification of mountain base elevation based on mountain structure modeling - Wenjie, Zhang; Mengyang, An; Guanhong, Chen; Fang, Zhao; Yong, Cheng; Jiale, Tang (Frontiers in Environmental Science, 2022)
The mountain base elevation (MBE), which refers to the initial altitude of mountain or mountain altitudinal belt, is of great significance for the study of mountain altitudinal zonality and mass elevation effect (MEE). However, a fast and efficient algorithm for the automatic extraction of MBE is still lacking. Therefore, a new method to calculate MBA based on mountain structure modeling is proposed in Qinling-Daba Mountains (QDM). The result shows that: 1) The mountain structures in different catchments of QDM can be divided into 6 types: pyramid, low-diamond, diamond, inverse pyramid, hourglass and ellipsoid, and each type has a specific distribution law; 2) Based on the mountain structure, the calculation result of MBE in QDM is 99-3979 m, and shows a distribution trend of high in the west and low in the east, high in the north and south and low in the middle, which is consistent with the overall terrain trend of QDM; 3) There is a good linear correlation between the mountain base elevation and the average altitude in QDM with R2=0.96 (p<0.01), which means that the MBE quantification algorithm based on mountain structure can well represent the complex mountain terrain which is closely related to the MEE, and reflects the important application value of the method to the research of mountain elevation effect.